Karawitan Composition Eka Semaya | Komposisi Karawitan Eka Semaya - I Kadek Widianatara Putra (GHURNITA: Jurnal Seni Karawitan, 2023)
Eka Semaya is a composition of karawitan petegak, which takes ideas from the stylist's personal experience. Eka Semaya is taken from the word Eka, which means One, and Semaya, which means Promise. So it can be concluded that Eka Semaya is a promise made by someone who is used to describe love and affection for the opposite sex, or it can be interpreted as a determination or a commitment between two humans (men and women) in which they make this Promise or determination in a wedding procession. This work creates stories about the stylist's and his partner's life journey. It is poured into a karawitan composition using the gamelan Semar Pegulungan Saih Pitu as the medium. The creation method used in Eka Semaya's karawitan designs is Alma M. Hawkins' method, which includes several stages: exploration, improvisation, and forming. Eka Semaya's composition is divided into four rounds, totaling 12 minutes. The realization of Eka Semaya's karawitan arrangements is expected to increase young Balinese artists' creativity to create works based on personal experience and have a value of beauty and features in compositional works.